Implantation: timing is everything. (1999)
Understanding the many facets of human reproduction has long been considered a guessing game. According to Allen Wilcox, chief of the Epidemiology Branch at the NIEHS, until now, knowing exactly when implantation of an egg into the uterine wall occurs has been impossible because the event has never been observed in humans. However, Wilcox and his team have recently taken some of the guessing out of the process by shedding light on how the timing of implantation may affect a pregnancy's outcome. The results of their research were published in the 10 June 1999 issue of the New England Journal of Medicine.